Preliminary studies on the characteristics of coir twines - Gopalan Nayar, S (Indian Journal of Fisheries, 2016)
Coir in the form of twines and ropes is a fishing gear material widely used,particularly in South India, for the fabrication of essential components ofseveral types of fishing implements. Very little information is on recordelucidating the essential dynamic characteristics of this important gearmaterial. Miyamoto and Shariff (1958) in an earlier communication havepresented certain details on the characteristics and rotting qualities of onevariety of coir twine. The present study on the characteristics of differentgrades of coir twines was undertaken at the instance of Dr. Miyamoto witha view to evaluate the qualities of the different grades of coir twines and tofacilitate determination of their utility as a fishing gear material.